Type 2 diabetes and metabolic syndrome: identification of the molecular mechanisms, key signaling pathways and transcription factors aimed to reveal new therapeutical targets - Ivan I. Dedov; Vsevolod A. Tkachuk; Nikolai B. Gusev; Vladimir P. Shirinsky; Aleksandr V. Vorotnikov; Tatiana N. Kochegura; Aleksander Y. Mayorov; Marina V. Shestakova (Сахарный диабет)
Type 2 diabetes mellitus (T2DM) is a socially important disease with only symptomatic therapy developed due to lack of knowledge about its pathogenesis and underlying mechanism. Insulin resistance (IR) is the first link of T2DM pathogenesis and results in decrease of ability of insulin to stimulate glucose uptake by target cells. Development of IR involves genetic predisposition, excessive nutrition, stress, obesity or chronic inflammation due to disruption of insulin signaling within cells. Molecular mechanisms and markers of IR are characterized rather poorly, which prevents early diagnosis and creation of preventive therapy. Euglycemic clamp test is still a golden standard for IR diagnosis in clinic. Hyperglycemia is a distant consequence of IR in which damaging effect of oxidative and carbonyl stress is realized and diagnosis of T2DM is stipulated. Molecular chaperones and small heat-shock proteins have a protective effect at the early stages of T2DM pathogenesis, preventing development of reticulum stress and apoptosis. Endothelial dysfunction is related to T2DM and its cardiovascular complications, however, it is unknown on which stage of pathogenesis these changes occur and what are their molecular inductors. Finally, transcriptional activity and adipogenic differentiation play an important role in formation of new fat depots from predecessor cells and activation of brown and “beige” fat demonstrating hypolipidemic and hypoglycemic properties. The aim of this study was investigation of pathophysiological mechanisms of development of IR and endothelial dysfunction, role of transcription factor Prep1 and small heat shock proteins, evaluation of novel methods of diagnostics of IR and therapeutic potential of brown and “beige” fat, determination of biotargets for new antidiabetic drugs.